Testis developmental related gene 1 (TDRG1) encodes a progressive motility-associated protein in human spermatozoa. Issue 2 (6th December 2020) - Chen, Houyang; Tang, Liang; Hong, Qing; Pan, Tingting; Weng, Shiqi; Sun, Jie; Wu, Qiongfang; Zeng, Xuhui; Tang, Yuxin; Luo, Tao
Abstract: STUDY QUESTION: Is there an association between the human testis-specific gene, testis developmental related gene 1 ( TDRG1 ) and human sperm motility? SUMMARY ANSWER: TDRG1 is associated with asthenozoospermia and involved in regulating human sperm motility. WHAT IS KNOWN ALREADY: Many testis-specific proteins potentially regulate spermatogenesis and sperm motility. We have identified a novel human testis-specific gene, TDRG1, which encodes a 100-amino-acid protein localized in the human sperm tail, yet little is known about its role in human spermatozoa. STUDY DESIGN, SIZE, DURATION: Sperm samples were obtained from normozoospermic men and asthenozoospermic men who visited the reproductive medical center at Jiangxi Maternal and Child Health Hospital, Nanchang, Jiangxi, China between February 2018 and January 2019. In total, 27 normozoospermic men and 25 asthenozoospermic men were recruited to participate in the study. PARTICIPANTS/MATERIALS, SETTING, METHODS: The level of TDRG1 in sperm of normozoospermic and asthenozoospermic men was examined by immunoblotting and immunofluorescence assays. Progressive motility was examined by computer-aided sperm analysis. The correlation between the TDRG1 protein level and progressive motility was analyzed by linear regression. TDRG1 was imported into the sperm of normozoospermic and asthenozoospermic men using a cell-penetrating peptide (CPP)-fused TDRG1 recombinant protein (CPP-TDRG1), and the progressive motility was examined. Also, the altered proteins associated with TDRG1 in asthenozoospermic sperm were detected using label-free quantification method-based quantitative proteomic technology. TDRG1-interacting proteins were identified by co-immunoprecipitation coupled with tandem mass spectrometry analysis. MAIN RESULTS AND THE ROLE OF CHANCE: The mean level of TDRG1 was significantly decreased in sperm of asthenozoospermic men compared with normozoospermic men ( P  < 0.05) and was positively correlated with percentage of progressively motile sperm ( r 2 = 0.75, P  = 0.0001). The introduction of TDRG1 into human sperm, using CPP, significantly increased progressive motility ( P  < 0.05) and improved the progressive motility of sperm from asthenozoospermic men to the normal level. TDRG1 forms a protein complex with sperm-motility related proteins in human sperm and its downregulation was associated with a decrease in other motility-related proteins. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: The sample size was limited and larger cohorts are needed for verifying the positive effect of CPP-TDRG1 on human sperm motility. Furthermore, the caution should be paid that a comprehensive safety examination would be performed to evaluate whether CPP-TDRG1 is a possible treatment approach for asthenozoospermia. WIDER IMPLICATIONS OF THE FINDINGS: Our results provide new insights into the mechanisms of sperm motility which may contribute to the diagnosis and treatment for asthenozoospermia. STUDY FUNDING/COMPETING INTEREST(S): National Natural Science Foundation of China (81501317 and 81871207 to H.C.; 81771644 to T.L.; 31671204 to X.Z.; 81571432 to Y.T.). The authors have no conflicts of interest to declare.